Information Technology Training in Building an Entrepreneurial Spirit - Muhammad Ferdiansyah; Anisa Martiah; Sevi Andriasari (LPPM Sekolah Tinggi Teknologi Nusantara Lampung, 2023)
Entrepreneurship is a process of creative and innovative activities to change commodity goods or services by taking advantage of opportunities and existing resources to generate added value in winning the competition. Creativity, innovation, and added value become keywords related to Information Technology to build Entrepreneurship. The ability of the community to use information technology, especially foreign language students and the general public, is still in the passive user order. These are problems that must be resolved because entrepreneurship today is multiplying thanks to information technology. From the aspect of understanding, partners also need to be equipped with skills in using information technology based on E-Commerce to develop entrepreneurial principles. Universities must participate in providing solutions to this problem through Information Technology training activities in Building Souls Entrepreneurship. This can be seen from the average gain score of participants' understanding of training activities of 0.63 which is in the moderate category. Taking into account the results of this training activity, This activity should be followed up with training or mentoring sustainability so that participants, in particular, and society, in general, will be skilled in creating and utilizing e-commerce-based business profiles to sharpen opportunities for entrepreneurial spirit development.